The effects of a controlled worksite environmental intervention on determinants of dietary behavior and self-reported fruit, vegetable and fat intake - Chin A Paw Marijke; van Poppel Mireille NM; Engbers Luuk H; van Mechelen Willem (BMC, 2006)
Abstract Background Eating patterns in Western industrialized countries are characterized by a high energy intake and an overconsumption of (saturated) fat, cholesterol, sugar and salt. Many chronic diseases are associated with unhealthy eating patterns. On the other hand, a healthy diet (low saturated fat intake and high fruit and vegetable intake) has been found important in the prevention of health problems, such as cancer and cardio-vascular disease (CVD). The worksite seems an ideal intervention setting to influence dietary behavior. The purpose of this study is to present the effects of a worksite environmental intervention on fruit, vegetable and fat intake and determinants of behavior. Methods A controlled trial that included two different governmental companies (n = 515): one intervention and one control company. Outcome measurements (short-fat list and fruit and vegetable questionnaire) took place at baseline and 3 and 12 months after baseline. The relatively modest environmental intervention consisted of product information to facilitate healthier food choices (i.e., the caloric (kcal) value of foods in groups of products was translated into the number of minutes to perform a certain (occupational) activity to burn these calories). Results Significant changes in psychosocial determinants of dietary behavior were found; subjects at the intervention worksite perceived more social support from their colleagues in eating less fat. But also counter intuitive effects were found: at 12 months the attitude and self-efficacy towards eating less fat became less positive in the intervention group. No effects were found on self-reported fat, fruit and vegetable intake. Conclusion This environmental intervention was modestly effective in changing behavioral determinant towards eating less fat (social support, self-efficacy and attitude), but ineffective in positively changing actual fat, fruit and vegetable intake of office workers.